Strategies to Improve the Barrier and Mechanical Properties of Pectin Films for Food Packaging: Comparing Nanocomposites with Bilayers - Souza, Victor Gomes Lauriano (2022)
2020.04441.BD SFRH/BD/144346/2019 UIDB/50006/2020 UIDP/50006/2020 UIDB/04077/2020 UIDP/04077/2020 UIDB /00100/2020